Bacteriostatic activities of garlic bulb, lemon peel and orange peel extracts against foodborne microorganisms in spaghetti meat sauce - Dela Rosa, Marie Jo J.; Gabriel, Alonzo Alulod (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
This study was conducted to characterize the bacteriostatic activities of garlic bulb- (GBE), ethanolic lemon peel- (ELPE), and ethanolic orange peel (EOPE) extracts against Escherichia coli O157:H7, Salmonella enterica serovars, Listeria monocytogenes, and Staphylococcus aureus in spaghetti meat sauce. The maximum permissible supplementation (MPS) levels of the extracts in a spaghetti formulation determined through sensory evaluations were 6.0% for GBE and 3.0% for ELPE and EOPE. However, the MPS of ELPE and EOPE did not inhibit any of the test organisms in the subsequent antimicrobial assays, with minimum inhibitory concentrations (MIC). Co-supplementation of 3.0% ELPE and EOPE with 3.0% GBE resulted in complete inhibition of all test organisms. Furthermore, these combinations inhibit microbial proliferation in inoculated spaghetti meat sauce at 31 ºC for 8 h. The results of this study may be used in controlling foodborne pathogens in spaghetti, which has been identified to be a common vector of illnesses in the Philippines.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Antibacterial agents; Plant extracts